PENGARUH LEVEL PEMBERIAN TEPUNG DAUN SIRSAK (ANNONA MURICATA LINN) DALAM RANSUM TERHADAP ORGAN DALAM AYAM PETELUR JANTAN (GALLUS DOMESTICUS) - Wasir Ibrahim; Ririn Novita (Universitas Muhammadiyah Tapanuli Selatan, 2020)
This study aims to determine the effect of the level of soursop leaf flour (Annona muricataLinn) in rations on internal organs in male laying hens (Gallus domesticus). The research method used was an experimental method using a Complete Randomized Design (CRD) arranged nonfactorial, with 6 levels of treatment 4 replications so that 24 experimental units were obtained, each experimental unit (each cage) was filled with 4 male laying hens. So in this study required 96 male-and-male (DOC) eggs. The treatments in this study were: U0 = Commercial Feed BR-1, U1 = 100% Commercial Feed without Soursop Leaf Flour, U2 = Commercial Feed 98% + Soursop Leaf Flour 2%, U3 = Commercial Feed 96% + Soursop Leaf Flour 4% , U4 = Commercial Feed 94% + Soursop Leaf Powder 6%, U5 = Commercial Feed 92% + Soursop Leaf Powder 8%. From the results of statistical data analysis it is known that the treatment of soursop leaf flour in rations on organs in Male Laying Hens has a significant effect on heart weight, but does not significantly affect heart weight, pancreatic weight and gizard weight.